2012
DOI: 10.1080/15533174.2012.680139
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, and Antimicrobial Activity of a Novel Trinuclear Cadmium(II) Complex Derived From 2-Ethoxysalicylaldehydethiosemicarbazone

Abstract: The Schiff base 2-ethoxysalicylaldehydethiosemicarbazone (HL) derived from 3-ethoxysalicylaldehyde and thiosemicarbazide, and its centrosymmetric trinuclear cadmium(II) complex [Cd 3 L 4 ]·2NO 3 ·2H 2 O, have been successfully prepared. The structure of the complex was characterized by elemental analyses, IR spectrum, and single-crystal X-ray crystallographic determination. The complex crystallizes in the monoclinic space group C2/c with unit cell dimensions a = 15.102(2) Å, b = 19.049(2) Å, c = 21.303(3) Å, β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The ethoxy derivative of salal thiosemicarbazone ligand was synthesized following a published procedure. 5 The metal precursors, [RuHCl(CO)(py)(PPh3)2], [RuHCl(CO)AsPh3)3] and [RuHCl(CO)(PPh3)3], were synthesized by reported procedure. [6][7][8] In a Vario EL III CHNS analyzer, microanalysis (elemental analysis) of the samples were performed.…”
Section: Methodsmentioning
confidence: 99%
“…The ethoxy derivative of salal thiosemicarbazone ligand was synthesized following a published procedure. 5 The metal precursors, [RuHCl(CO)(py)(PPh3)2], [RuHCl(CO)AsPh3)3] and [RuHCl(CO)(PPh3)3], were synthesized by reported procedure. [6][7][8] In a Vario EL III CHNS analyzer, microanalysis (elemental analysis) of the samples were performed.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11] Mainly, condensation products of 3-ethoxysalicylaldehyde were effective cytotoxic ligands on HepG2, HCT116, and MCF-7 cells. 12 In addition, antimicrobial effects of 3-ethoxysalicylaldehyde [13][14][15] and 2-amino-4chlorophenol-derived Schiff bases are reported. 16,17 Therefore in this study, it was found worthy of investigating the anticancer activity of a Schiff base, (E)-4chloro-2-((3-ethoxy-2-hydroxybenzylidene)amino)phenol (ACES), which is a condensation product of 2-amino-4-chlorophenol with 3-ethoxysalicylaldehyde.…”
Section: Introductionmentioning
confidence: 99%